PENGARUH FAKTOR – FAKTOR DALAM PERSPEKTIF FRAUD TRIANGLE TERHADAP KECURANGAN PELAPORAN KEUANGAN (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2016 – 2019) - Ratna Herawati; Amalia Nur Chasanah; Masitha Fahmi Wardani; Risanda Alirastra Budiantoro (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
This study empirically examines the effectiveness of Cressey’s (1953) fraud risk factor framework adopted in SAS No. 99 in detection of financial statement fraud. According to Cressey’s theory pressure, opportunity and rationalization are always present in fraud situations. The variables of the fraud triangle used is pressure proxied by ACHANGE, FREEC, and FINANCE, opportunity proxied by BDOUT, TRN, and CEO_TRN, rationalization proxied by AUDSWITCH. This population of study was company listed on the Stock Exchange, and then the samples were taken by purposive sampling criteria the company’s corporate criteria sanctioned from Otoritas Jasa Keuangan. The total sample of 106 companies that the company is comprised of 49 companies that commit fraud financial reporting and 57 companies that are not financial reporting fraud by the similarity of firms in the industry, the year and the amount of total assets of the company. This study uses logistic regression statistical. The results of this study indicate that the opportunities proxied by TRN and CEO_TRN, rationalization proxied by AUDSWITCH effect on financial statement fraud and pressure are proxied by ACHANGE, FREEC, FINANCE and opportunities proxied by BDOUT no effect on financial statement fraud.